SAW sensor for NO2 detection utilizing the dynamic characteristic of the device - JAKUBIK, W.; URBAŃCZYK, M. (Archives of Acoustics, 1996)
A surface acoustic wave (SAW) sensor for NO2 detection with CuPc and PbPc layers, based on the dynamic characteristic of the lowest frequency mode has been developed. For the investigated concentrations range the changes in the device response, Δf=f-f0, were very large (from a few kHz to even 10 kHz), which resulted in a "jumping" of the generation system to the next frequency modes. Thus, we were not able to observe the saturation levels for the investigated concentrations and prepared phthalocyanine layers. Therefore, we decided to determine the NO2 concentration after 480 s from the moment when gas was allowed to flow through the measuring chamber. At a constant gas flow rate we have obtained a good linear dependence between the device output signal and the NO2 concentration in pure air. In the case of CuPc films (0.27 μm and 0.72 μm) the greatest sensitivity (130 Hz/ppm) has been obtained at a thinner layer and a higher gas flow rate. The sensitivity of the investigated PbPc layer (0.083 μm) was much higher (from 1200Hz/ppm at 27°C to 2000 Hz/ppm at 70°C), thus was had to use a small concentration range (from 0.6 to 3.2 ppm NO2) in order to maintain oscillations for at least 480 s. Besides, the response of the device depends on temperature. At a higher temperature the magnitude of the response was greater and the response time shorter at this same gas concentration.